2023
DOI: 10.1002/cssc.202300133
|View full text |Cite
|
Sign up to set email alerts
|

Biomass to Aromatic Amine Module: Alkali Catalytic Conversion of N‐Acetylglucosamine into Unsubstituted 3‐Acetamidofuran by Retro‐Aldol Condensation

Abstract: Aminofurans are widely used in drug synthesis as aromatic modules analogous to aniline. However, unsubstituted aminofuran compounds are difficult to prepare. In this study, a process for the selective conversion of N‐acetyl‐d‐glucosamine (NAG) into unsubstituted 3‐acetamidofuran (3AF) is developed. The yield of 3AF from NAG catalyzed by a ternary Ba(OH)2−H3BO3−NaCl catalytic system in N‐methylpyrrolidone at 180 °C for 20 min can reach 73.9 %. Mechanistic studies reveal that the pathway to 3AF starts with a bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…discovered a ternary Ba(OH) 2 -H 3 BO 3 -NaCl catalytic system to convert NAG to 3AF. 102 According to the control experiments and the high performance liquid chromatography-mass spectrometry analyses, 3A5AF was not the intermediate for 3AF. On the contrary, it is deduced that the NAG first underwent retro-aldol condensation at the C4-C5 position to afford glycolaldehyde and NAE.…”
Section: Dehydrationmentioning
confidence: 94%
“…discovered a ternary Ba(OH) 2 -H 3 BO 3 -NaCl catalytic system to convert NAG to 3AF. 102 According to the control experiments and the high performance liquid chromatography-mass spectrometry analyses, 3A5AF was not the intermediate for 3AF. On the contrary, it is deduced that the NAG first underwent retro-aldol condensation at the C4-C5 position to afford glycolaldehyde and NAE.…”
Section: Dehydrationmentioning
confidence: 94%
“…An efficient protocol involving 3A5AF for the preparation of functionally rich 3-amidofurans, which are valuable functionalized N-containing substances from chitin, was developed by Sperry’s group . Gan et al recently reported the valorization of NAG to unsubstituted 3-acetamidofuran . Liu and co-workers developed ionic-liquid-based systems for LA production from chitin and even crab shells. , The dehydration of N -acetylglucosamine to enantiopure dihydroxyethyl acetamidofuran was recently reported by Minnaard and co-workers .…”
Section: Introductionmentioning
confidence: 99%
“…55 Gan et al recently reported the valorization of NAG to unsubstituted 3-acetamidofuran. 56 Liu and co-workers developed ionic-liquid-based systems for LA production from chitin and even crab shells. 57,58 The dehydration of N-acetylglucosamine to enantiopure dihydroxyethyl acetamidofuran was recently reported by Minnaard and co-workers.…”
Section: ■ Introductionmentioning
confidence: 99%